Assessment of water quality of the Brahmaputra River in India for irrigation purpose - RAY, PRASENJIT; SARMAH, SUSMITA; MOURYA, K.K.; JENA, R.K.; SHARMA, G.K.; HOTA, S.; SHARMA, R.P.; DAS, BACHASPATI; RAY, S.K. (Journal of Soil and Water Conservation, 2023)
The importance of the water resources of the Brahmaputra River in the agricultural sector of the transboundary Ganges-Brahmaputra-Meghna (GBM) region of the South and East Asia is enormous. For the effective utilization of such water resources for agricultural and allied activities, assessment and monitoring of the water quality are of practical importance, since the usability of any water resource depends on many quantifiable parameters. In the present study, water quality of the Brahmaputra River was determined in order to assess the suitability of the water resources for irrigation purpose. For this purpose, twenty-one geocoded water samples were collected from the main course of the Brahmaputra River and its tributaries at different locations in Arunachal Pradesh and Assam in India. Important chemical parameters of the collected water samples were analysed in the laboratory and water quality indices were also computed. Assessment of the water quality indicated that 62% of the water samples were found unsuitable for irrigation purpose due to high magnesium and bicarbonate concentration. Such findings emphasize that periodic assessment and monitoring of water quality of the Brahmaputra River is essential as far as agricultural and allied activities are concerned in the GBM basin. The findings of the present study would be useful for efficient management of water resources for appropriate use in the GBM region.